Examination of heart rate variability in young swimmers - Taskin, B. S.; Taskin, M.; Taskin, M.; Taskin, H. (Medicina dello Sport, 2021)
BACKGROUND: Heart rate variability (HRV) is the ripples in the time intervals between adjacent heartbeats. METHODS: The aim of this study was to examine the HRV in the swimmers. We can describe 24 hours, short-term, (~5 min) or brief, and ultra-short-term (<5 min) HRV using time-domain, frequency-domain, and non-linear measurements. A total of 35 male swimmers (age mean; 12.10±1.758 years, height mean; 1.51±0.124 m, body weight mean; 43.81±13.93 kg and sport age mean; 3.20±1.416 years) participated in the study. The HRV was recorded with a V800 waterproof GPS polar hours for 2 minutes resting, swimming and after swimming. RESULTS: Mean of the RR intervals (MeanRR) value after swimming was found to be higher than the MeanRR value obtained during swimming (P<0.05). The resting root mean square of successive RR interval differences (RMSSD) value was lower than the RMSSD value obtained swimming (P<0.05). Percentage of successive RR intervals that differ by more than 50 ms. (pNN50) values obtained swimming were found to be higher than resting and after swimming values of pNN50 (P<0.05). In addition, pNN50 values obtained resting were higher than pNN50 values obtained after swimming (P<0.05). The low frequency (LF)/high frequency (HF) value obtained after swimming was found to be higher than the LF/HF value obtained resting (P<0.05). CONCLUSIONS: It is observed that the power of the contraction of the heart and the anabolic activities did not change resting, swimming, and after swimming. It is thought that the subjects were not exposed to the stress resting, swimming, and after swimming. The balance between sympathetic and parasympathetic functions is preserved swimming and resting, it is found that this equilibrium after swimming is about 4 times changed compared to the previous case. At time-domain values, it is thought that the balance between the brain and the heart is more disturbed in heart rate variability swimming.